1997
DOI: 10.1121/1.417992
|View full text |Cite
|
Sign up to set email alerts
|

Perception of nonlinear and linear formant trajectories

Abstract: Perception of F2 trajectories in synthetic vowels was investigated. Perceptual boundaries (50% response points of identification functions) of 20-step/U-I/continua with various shapes of F2 trajectories were determined and compared with the boundary for vowels with steady-state F2. In experiment 1, the vowels were synthesized in either/j-j/or/w-w/context resulting in parabolic trajectories, then the stimuli were split into halves resulting in quadratic F2 trajectories. All stimuli were 200 ms long. For the/wVw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
(4 reference statements)
4
11
0
Order By: Relevance
“…Relative to the steady-state condition, more /I/ responses were obtained for the /wVw/ context and more / ʊ / responses were obtained for the /jVj/ context. Similar context-dependent vowel categorization has subsequently been demonstrated by Nearey (1989) using stop consonant contexts (/bVb/ vs /dVd/) and by Nabelek and Ovchinnikov (1997), using isolated vowels versus /wV/ contexts (with no steady-state portion).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Relative to the steady-state condition, more /I/ responses were obtained for the /wVw/ context and more / ʊ / responses were obtained for the /jVj/ context. Similar context-dependent vowel categorization has subsequently been demonstrated by Nearey (1989) using stop consonant contexts (/bVb/ vs /dVd/) and by Nabelek and Ovchinnikov (1997), using isolated vowels versus /wV/ contexts (with no steady-state portion).…”
Section: Introductionsupporting
confidence: 63%
“…The frequency of F2 increased in 10 Hz steps from 1000 to 2500 Hz. These endpoint values matched the stimuli used by Nabelek and Ovchinnikov (1997). Lindblom and Studdert-Kennedy (1967) and Williams (1986) varied their F3 frequency as a function of F2.…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…Carré et al (1994) manipulated synthesized formant patterns and found that perception of the vowel /a/ was affected only when the formant frequencies were far from canonical for this vowel. Nábělek and Ovchinnikov (1997) compared the perception of linear and quadratic vowel formants and found that a vowel identifi er categorized the differing vowel contours as the same. Pitermann (2000) concluded that steady-state portions of vowels alone serve better than dynamic aspects alone in modeling vowel perception in French, though this generalization may not hold for English.…”
Section: Bey Ond the Steady Statementioning
confidence: 99%